Antioxidant and Cytotoxic Properties of Extract from Soil Bacteria Isolated from Muna Island, Southeast Sulawesi - Priyanto, Jepri Agung; Hening, Egiyanti Nur Widhia; Permatasari, Vera; Prastya, Muhammad Eka; Hasidu, La Ode Abdul Fajar; Primahana, Gian (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2024)
Soil bacteria could be the promising source of secondary metabolites with diverse pharmacological activities. Bacteria coded as P1 and M7 were isolated from soil obtained from Muna Island, Southeast Sulawesi. This research aimed to evaluate the antioxidant activity, cytotoxic property, and identify the chemical profile of the extract derived from soil bacteria P1 and M7. Based on 2,2'-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid (ABTS) and 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay, extract derived from P1 isolate was moderately active against ABTS free radical with IC50 of 126.22±10.82 µg/mL, and less active on DPPH (IC50: 721.95±16.59 µg/mL), while M7 extract was less active towards DPPH and ABTS. Interestingly, these extracts in the concentration of 100 µg/mL were cytotoxic to breast cancer cell (MCF-7), as tested by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-2H-tetrazolium bromide (MTT) assay. MCF-7 viability was decreased up to 69.83±1.46 % and 61.49±0.76 % after treated with P1 and M7 extract, respectively. The extracts were also induced membrane disruption and apoptosis of MCF-7 cells. The extracts contained phenol (9.52±0.22 and 10.41±0.09 mg EAG/g extract, for P1 and M7, respectively) and flavonoids (9.16±0.16 and 9.29±0.24 mg EQ/g extract, for P1 and M7, respectively). According to Gas Chromatography Mass Spectrometry (GC-MS) analysis, Pyrrolo[1,2-a] pyrazine-1,4-dione, hexahydro-3-(2-methylpropyl) that previously well known as antioxidant and cytotoxic compounds, were found in the M7 and P1 extract. This compound may play a vital role in the radical scavenging and cytotoxic properties of P1 and M7 extracts. The results of this study indicate that P1 and M7 extracts could be the potential source of antioxidant and cytotoxic compounds and need to be further developed for pharmaceutical use.